Biogenic Volatile organic compounds Emission in Malaysian Landscapes and its implication to the Global Carbon cycle - Mohd Noh Dalimin; Alona C Linatoc; Maryati Mohamed, Datin (Universiti Malaysia Sabah, 2009)
Emissions of biogenic volatile organic compounds from vegetation are recognized due to their importance in influencing the chemical and physical properties of the atmosphere. To date, very limited studies in tropical plants have been included in the regional and global inventories of emissions, albeit their role in the global carbon cycle; tropical rainforest is the major sink of carbon dioxide on Earth. This study aims to understand the carbon balance over tropical landscapes by determining how much carbon is being absorbed by vegetation and how much is being emitted back to the atmosphere in the form of biogenic volatile organic compounds in different vegetation landscapes, i.e. primary forest, secondary forest, and oil palm plantations. Results of this study showed that the primary and secondary forests of Danum Valley, Sabah, Malaysia have similar isoprene emission potentials of 2,164 g km-2 hr-1 and 2,012 g km-2 h(t, respectively, while the isoprene emission potential of oil palm plantation is 19,500 g km-2 h(l. Isoprene emissions from oil palms are highly dependent to temperature. In terms of species emission potentials, Dipterocarps that dominate the tropical rainforest are non-isoprene emitter but monoterpene emitters, while most of the pioneering plants (Euphorbiaceae, Zingiberaceae) are both isoprene and monoterpene emitters. The sources of isoprene emission from primary forest are from Moraceae, leguminosae, and Clusiaceae, among others. This study conclude that tropical rainforest of Danum Vally, Sabah, particularly the oil palm plantations are significant sources of biogenic volatile organic compounds and should be considered in regional and global carbon modeling. This study also highlights the need for more studies on the behavior of tropical plants as far as emission of biogenic volatile organic compounds, especially under stressed conditions.